The Economic Concept of Education in Islam - Holilur Rahman; Muhammad Syaiful Islam; A Hasib; Ali Wafa (ORGANIZE: Journal of Economics, Management and Finance, 2024)
This paper explains the concept of education economics in Islam. The economics of education in Islam has a purpose: to reflect the principles and values of Islam, and its goals involve social, economic, and moral aspects. In addition, there are also economic uses of education in Islam, namely: involving its contribution to the social, economic, and moral development of society. The concept of educational economics in Islam is based on ethical principles and Islamic values that include justice, empowerment, and blessings. Some of the main aspects of the concept are: involving education, wealth distribution, and social responsibility. In addition, there are several important points in the concept of education economics in Islam, namely the importance of education, justice in wealth distribution, economic empowerment, prohibition of riba (interest), social responsibility, sustainable economic growth, transparency and accountability, respect for employment, development.